Theoretical and methodological basis of training of entrepreneurs in the system of economical education (Pedagogy of Higher and Secondary Education, 2013)
Madzygon V. V. Theoretical and methodological basis of training of entrepreneurs in the system of economical education.The article observe an important issue of current interest of the necessity of training of entrepreneurs in the system of continuous economical education, of education of students; those knowledge of economical disciplines could be used in practical activities at the labor market, in different fields of social needs for increasing of the wealth of state and society.
Keywords: market economy; economical education; entrepreneurship; entrepreneurs; professional competence; labor market